PENGARUH FINANCIAL STABILITY, CHANGE IN AUDITORS, DCHANGE, CEO’s PICT PADA FRAUD DALAM PERSPEKTIF FRAUD PENTAGON - Alfian, Nurul (Fakultas Ekonomi, Program Studi Akuntansi, 2020)
This research aims to obtain empirical evidence about effectiveness of the fraud pentagon are pressure, opportunity, rationalization, competence and arrogance in detecting financial statement fraud. The variables of the fraud pentagon that used is a pressure with proxy financial stability (ACHANGE), rationalization with change in auditor, competence with chnage in director’s, and arrogance with Frequent Number of CEO’s Picture . In this research to detecting financial statement fraud as the dependen variabel. The population of this research is the industries companies listed in Indonesia stock exchange in 2015-2017. Data analysis was performed with the classical assumption and hypotesis testing using linear regression. The result of this research indicates that the financial stability (ACHANGE), change in auditor (CPA), change in directors (DCHANGE), Frequent Number of CEO’s Picture (CEOPICT) influence the financial statement fraud,